2011
DOI: 10.1111/j.1468-3083.2011.04068.x
|View full text |Cite
|
Sign up to set email alerts
|

Finger retronychias detected early by 3D ultrasound examination

Abstract: Artículo de publicación ISIBackground A new pattern of ingrown nail, called retronychia is involved in the posterior translation of the whole nail unit producing paronychia. Objective To demonstrate an unusual case of paronychia that affected three of the fingers on the right hand. Methods We used 3D ultrasound to study the whole nail unit in the fingers of both the affected (right) and non affected (left) hand. Results Backward motion of the nail unit with decreased distance between the origin of the nai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 6 publications
1
31
0
Order By: Relevance
“…This abnormality can also appear as a total or partial posterior embedding of the nail unit. 3D ultrasound has been reported as being useful in the early detection and better clinical understanding of retronychia [ 10,11 ] (Figs. 18.6 and 18.7 ).…”
Section: Retronychiamentioning
confidence: 98%
“…This abnormality can also appear as a total or partial posterior embedding of the nail unit. 3D ultrasound has been reported as being useful in the early detection and better clinical understanding of retronychia [ 10,11 ] (Figs. 18.6 and 18.7 ).…”
Section: Retronychiamentioning
confidence: 98%
“…In addition, in nail psoriasis, there are other concomitant US signs, such as hypoechogenicity and increased thickness of the nail bed, loss of definition of the ventral plate, hyperechoic deposits in the ventral plate, loss of definition of both plates, and wavy and thickened plates. All of these signs differ greatly from the US findings for retronychia . However, a psoriatic nail can develop retronychia, particularly in late or severe stages; therefore, we must be aware to recognize these entities on US.…”
Section: Discussionmentioning
confidence: 88%
“…Retronychia is a nail disorder characterized by embedding of the proximal nail plate into the proximal nail fold, which clinically appears as an apparent halt to nail growth with a chronic proximal paronychia . It may be an underestimated condition that can appear after or concomitant to a severe illness, can be related to stress‐relevant situations, can be secondary to trauma, including sports injuries, or can appear as an idiopathic episode . Additionally, it has been reported that retronychia may have a similar etiology as Beau lines and onychomadesis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The new nail plate growth is often normal and the recurrences are not seen as in lateral ingrowth of nail plate. Wortsman et al [2] reported a case of triple finger retronychia resulting from trauma and the diagnosis was established using 3D ultrasonography (USG).…”
mentioning
confidence: 99%